Bio-ecology of Tea Mosquito Bug, Helopeltis Theivora (Waterhouse), an Emerging Pest of Red Cherry Pepper Capsicum annum Var. Cerasiforme in Sikkim Himalaya - Kalita, H.; Gopi, R.; Avasthe, R. K.; Yadav, A. (Indian Journal of Hill Farming, 2019)
The bio-ecology of tea mosquito bug, Helopeltis theivora (Waterhouse) an emerging pest of Red Cherry pepper Capsicum annum var. Cerasiforme was studied during 2010-2014 both in the field and laboratory conditions at ICAR Sikkim Centre, Tadong. Maximum no. of spots per day (97.8) was produced by the first instar nymph of H. theivora whereas the adult female caused maximum damage on the leaves (296.36 sq. mm/day). First leaf (youngest leaf) was most preferred by the first instar nymphs whereas second and third leaves were preferred by the second and third instar nymphs and fourth instar nymph and adults, respectively. The incubation period recorded was 7.8±0.78 days. The duration of first, second, third and fourth in stars were recorded as 3.3±0.48, 4.2±0.62, 3.2±0.58 and 4.8±0.64 days, respectively. It was observed from the study that the male survived for longer period 17.7±2.86 days in comparison to the female (15.3±2.50 days). The average life cycle of male and female was 41.0 ± 3.36 days and 38.6±3.12 days, respectively during July-August. The pre-oviposition period (4.6±0.51 days), oviposition period (9.6±1.23 days) and fecundity (81.5±5.32) were recorded in Red Cherry pepper. Hatching %, adult emergence %, reproductive success % and total growth index of H. theivora were recorded as 44.4±5.57, 48.4±6.18, 20.8±2.25 and 3.12±0.34, espectively. The correlation studies revealed that minimum temperature, relative humidity (maximum and minimum), total rainfall and no. of rainy days had significant positive correlation with the bug population and their feeding intensity whereas the duration of sunshine hours showed significant negative relation. Besides Red Cherry pepper, 13 another new alternate hosts of H. theivora have been identified in Sikkim.